Perlindungan Hukum Wisatawan Atas Penguasaan Fasilitas Peristirahatan Oleh Pelaku Usaha di Kawasan Wisata Magetan - ozha tiwa hiawananta (Jurnal Hukum Lex Generalis, 2024)
The control exercised by business actors over supporting facilities in rest areas must be a serious concern, as it infringes upon tourists' rights. This research is analyzed using a normative legal method with an inconcrete approach and analytical descriptive elaboration, exploring the freedom rights of tourists in utilizing supporting facilities, the obligations of vendors as business actors to provide comfort to tourists, and the legal consequences of violations of tourists' rights. The findings indicate that, according to Law Number 1 of 2009 on Tourism, tourists' rights to comfort in using supporting facilities are regulated, along with the obligations of business actors to provide comfort to tourists. Additionally, legal consequences in the form of sanctions are found in Magetan Regency Regional Regulation Number 7 of 2013 on Tourism.